BASIC DIDACTIC PRINCIPLES OF EDUCATION OF FORMATION OF MATHEMATICAL IMAGINATION IN PRESCHOOL CHILDREN - Nomoz Kholmirzayev (Galaxy International Interdisciplinary Research Journal, 2023)
The history, current state and modernity of the theory of the method of forming mathematical ideas. Based on the requirements of the Law of the Republic of Uzbekistan "On Education", the Law of the Republic of Uzbekistan "On Preschool Education and Training" and the State Curriculum "Ilk Kadam" The main goal of education is to educate the young generation as a healthy, comprehensively developed person based on the ideology of independence and to prepare them for school education.